A Novel Composite Poly-p-Phenylenebenzobisoxazole (PBO) Fiber Including Molecularly-Dispersed Copper Phthalocyanine in the Structure. Issue 8 (2nd August 2016) - Kitagawa, Tooru; Abe, Yukihiro; Kiriyama, Kohei
ABSTRACT: The possibility to make a composite poly- p -phenylenebenzobisoxazole (PBO) fiber including a second component without distorting its original structures and mechanical properties was examined. Copper phthalocyanine was found to fulfill the above-mentioned condition and can be dispersed in the fiber molecularly. It was shown that part of the embedded copper phthalocyanine can be aligned one-dimensionally with periodicity along the fiber axis in the fiber. The color of the resultant fiber was dark blue, which is different from the original fiber having its yellowish golden color. According to X-ray diffraction analysis the preferential orientation of the a-axis of the PBO crystal was slightly more oriented by the addition of copper pthalocyanine than that of the pure PBO fiber, but the crystal size of PBO wasn't also affected. We thus show the possibility of adding a second material that can add additional properties to the fiber, but keeping the original high mechanical properties and oriented structures.